PECULIARITIES OF CLINICAL MANIFESTATIONS OF CORONARY HEART DISEASE IN MEN AT A YOUNG AGE - Khasanjanova Farida Odilovna; Yusupova MokhinabonuFarukhovna; Khudoynazarov DalerAnvaro’g’li (Scholar Express Journals, 2022)
This study investigated the clinical features of coronary heart disease (CHD) in men at a young age. The study included 230 patients with CHD hospitalized in the Cardiac Intensive Care, Emergency Department #1 and #2 of Samarkand Branch of Republican Scientific Center for Emergency Medical Care (SF RSCEMC) during the period 2018-2021. The patients were divided into 2 groups according to their age. The 1st main group included 126 patients of young age. The 2nd comparative group included 104 elderly patients. The results showed that the occurrence of angina attacks from 6 to 8 times during the day was observed in 85 (67.5%) patients in Group 1, 82 (78.8%) patients in Group 2, which indicated the severity of the disease.
Keywords: CHD; ECG; EchoCG; ischaemia